Merawat Bumi Rahim Kehidupan Kita: Imperatif Iman, Implikasi Etis - Rahmat, Paul (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2016)
The present article discusses the grave ecological disaster we are facing today, such as drought, flood, typhoon, deforestization, desertification, polution of water-air-land, and the like, which is called an ‘ecozoic period’. It means a terminal of the history of the earth, which has put humanity at the cross-road, either choosing to act or letting all perish. The writer, on the one hand, acknowledges that scientific datas have helped people to comprehend better the ecological crisis. On the other hand, he also underlines that faiths and religious convictions have provided people inspirations and motivations to handle the problems. The crucial question then is: “What is the contribution of the Christian faith, particularly the universal salvation in Jesus Christ, to respond this ecological crisis and the crisis of life resources?” The writer is convinced that Christian faith –theology of creation, incarnation, cross, and resurrection– has enhanced the believers to involve and participate in safeguarding the earth. This faith has surely ethical implications, such as the spiritual, socio-cultural, and political dimensions or contemplation, ecological asceticism, and prophetical voices. These three ethical implications could reinforce the solid social movement toward a serious ecological conversion.